Conocimiento y práctica del autoexamen mamario en mujeres de 20-50 años: Centro de Salud Cordero Crespo, enero – mayo 2025 - Borja Sánchez, Daniela Julissa (2025)
Breast cancer is one of the leading causes of death in women worldwide, and early detection is essential for reducing mortality. Breast self examination is a complementary strategy that allows for early identification of abnormalities; however, its practice remains deficient in rural settings. Within this framework, this study aimed to evaluate the level of knowledge and practice of breast self-examination among women aged 20 to 50 attending the Cordero Crespo Health Center, with the aim of promoting self-care as a prevention tool. A quantitative approach was applied, with a descriptive, field based, and cross-sectional design. The sample consisted of 143 women selected through non-probability sampling. The instrument used was a questionnaire validated by expert judgment and administered with informed consent. The results showed that 72% of participants had a low level of knowledge about breast self-examination and 65% did not practice it regularly. A direct relationship was evident between lack of knowledge and lack of practice. It is concluded that there is an urgent need to implement educational strategies from the nursing field to empower women in their breast health care. It is recommended that information campaigns in primary care with a preventive focus be strengthened.